Existential and Mindfulness–Based Intervention to Increase Self-Compassion in Apparently Healthy Subjects (the EXMIND Study): A Randomized Controlled Trial - Sakai, Akari; Terao, Takeshi; Kawano, Nobuko; Akase, Mari; Hatano, Koji; Shirahama, Masanao; Hirakawa, Hirofumi; Kohno, Kentaro; Inoue, Ayako; Ishii, Nobuyoshi (Frontiers in Psychiatry, 2019)
Objectives: Mindfulness is a method of training the regulation of attention with non-judgmental acceptance that is linked to beneficial effects on health. The existential approach supports the uniqueness of each individual and helps to provide meaning to their lives. In this randomised controlled trial, we examined whether mindfulness-based intervention (MBI) and the existential approach could be combined sequentially and whether they operated antagonistically or cooperatively. Methods: One hundred thirty-seven participants aged 20 years or older without any severe mental disorders were randomly assigned (1:1), via an envelope method, to receive either 8-week MBI (N=68) or 4-week MBI followed by 4-week existential approach (EXMIND)(N=69). Participants were first allocated to a waiting-list group and subsequently randomised to the MBI group or EXMIND group. The primary outcome was self-compassion scale (SCS) total scores at 0, 4, and 8 weeks during intervention or waiting. The analyses were performed by linear mixed models for both primary and secondary outcomes following the intention-to-treat principle. Results: Both MBI and EXMIND groups had significantly increased SCS total scores compared to those of the waiting group, with mean SCS total scores of 2.3 (SD 3.0) in the MBI group and 2.1 (2.9) in the EXMIND group versus 0.3 (2.2) in the waiting group. Conclusions: Our findings suggest that MBI followed by existential approach are not antagonistic and may have cooperative effects, suggesting that EXMIND may be a useful treatment.